Análise de dados de Geomagnetismo registados no Observatório Magnético de Coimbra em 1969 - Duque, Maria Rosa (2019)
In this work data on the geomagnetic field recorded at the Magnetic Observatory of the University of Coimbra during the year 1969 are analysed. The reason for the work is the occurrence of an earthquake of magnitude Mw = 8.0 in February 28th and two earthquakes of magnitude 5.5 and 5.8 with focus on the SW of Cape Saint Vincent on May 5th and September 6th . The data allows detecting a decrease in the horizontal component of the field on the date of the 3 earthquakes and a relative increase in the vertical component. A great increase in the declination value was observed on February 27 th.